The Relevance of Skill Development in the Indian Context - Subramaniam, D.; Ben, John Ben (Arthshastra Indian Journal of Economics & Research, 2018)
India is a diverse country and many initiatives of the Government of India are aimed at achieving an economic growth that is also inclusive. While aiming to accelerate the economic growth to a sustainable level, the emphasis has also been on achieving a growth which was inclusive. India opted for liberalization in 1990-1991 and subsequent to that, irrespective of the political party in power, there has been some amount of continuation of such initiatives. This paper aimed at deliberating the salient initiatives of the Government of India in the last few years in a critical way with a focus on skill development, and it captured the implications of such initiatives on the society and also on business. The paper also brought out the course corrections needed on the basis of likely deviations of the intended impacts. Though a lot of research material is available on the need for an inclusive growth for a country like India, a comprehensive research was needed to understand what the challenges were for such an approach. This paper aimed to identify such gaps and deliberated the same and suggested possible course corrections. Such a body of knowledge would ignite thinking at all levels with the sole objective of making India great. A relevant comparison of India was made with China to understand and explore adopting similar approaches that enabled China to taste success or desist from approaches that did not help.